Найдите производную 1-ого и 3-его примеров.

0 голосов
19 просмотров

Найдите производную 1-ого и 3-его примеров.


image

Алгебра (50 баллов) | 19 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

1) f(x)= x^{2} + \sqrt[3]{x^2}= x^{2} + x^{2/3}
f'(x)=2x+ \frac{2}{3}*x^{2/3-1}=2x+ \frac{2}{3} *x^{-1/3}=2x+ \frac{2}{3 \sqrt[3]{x} }
3) f(x)=(x+ \frac{1}{ \sqrt{x} } )(x^2-3x-8)=(x+x^{-1/2})(x^2-3x-8)
f'(x)=(1- \frac{1}{2}*x^{-3/2} )(x^2-3x-8)+(x- \frac{1}{ \sqrt{x} } )(2x-3)
Можешь дальше раскрыть скобки, если хочешь.

(320k баллов)